International marketing research opportunities and challenges in the 21st century - Rialp, Alex; Rialp, Josep (Elsevier JAI, 2007)
This book presents a collection of original, high-quality essays in international marketing. Both theoretical/conceptual and empirical contributions are included. Written by scholars from all over the world, these essays address various aspects of export and multinational marketing. While some authors focus on managerial issues in international marketing, others take a public policy or comparative perspective. Similarly, while some authors may confine their analysis to well-established concepts or methodologies in international marketing, others have the opportunity to incorporate new and innovative perspectives. It examines international marketing from theoretical and practical perspectives, and addresses various aspects of export and multinational marketing through management, public policy, and other issues.
Keywords: Export marketing -- Congresses.; Internet marketing -- Congresses.; elektronické knihy; electronic books